Identification of 28 DNA fragments that detect RFLPs in 13 distinct physical regions of the short arm of chromosome 5. - Overhauser, J (1987)
A series of 175 lambda phage carrying human inserts isolated from a library that is specific for the short arm of human chromosome 5 (5p) have been regionally mapped on 5p using a deletion mapping panel of 16 human-hamster cell hybrids, each of which contains a chromosome 5 with a different deletion in the short arm. Seventy-five single copy DNA fragments were screened with 12 restriction enzymes for their ability to detect restriction fragment length polymorphisms (RFLPs). Twenty-eight of these DNA fragments, which are located in 13 distinct physical regions of 5p, were found to detect RFLPs. These DNA markers make it possible to construct a linkage map that will span the entire length of 5p and will allow the relationship between genetic and physical distance for this region of the genome to be examined at a high level of resolution.